(untitled) (American International Journal of Business and Management Studies, 2019)
This study examines financial deepening, financial intermediation and Nigerian economic growth. The main purpose is to examine the relationship between financial deepening and Nigerian economic growth while the specific objectives are to examine the impact of interest rate, capital market development, rational savings, credit to private sector and broad money supply on the growth of Nigerian. Secondary data of the variables were sourced from the publications of Central Bank of Nigeria (CBN) from 1981-2017. Nigerian Real Gross Domestic Product (RGDP) was used as dependent variable while Broad money supply (M2), Credit to Private Sector (CPS), National Savings (NS), Capital Market Capitalization (CAMP) and Interest Rate (INTR) was used as independent variables. Multiple regressions with E-view statistical package were used as data analysis techniques. Cointegration test, Augmented Dickey Fuller Unit Root Test, Granger causality test was used to determine the relationship between the variable in the long-run and short-run. R2, F – statistics and β Coefficients were used to determine the extent to which the independent variable affects the dependent variable. It was found from the regression result that Broad Money Supply, credit to private sector have position effect on the growth of Nigerian Real Gross Domestic Product while National Savings, Capitalization and Interest Rate on Nigeria Real Gross Domestic Product. The co-integration test revealed presence of long-run relationship among the variables, the stationary test indicated stationarity of the variables at level. The Granger Causality Test found bi – variant relationship from the dependent to the independent and from the independent to the dependent variables. The regression summary found 99.0% explained variation, 560.5031, F – statistics and probability of 0.00000. From the above, the study concludes that financial deepening has significant relationships with Nigerian economic growth. We recommend that government and the financial sector operators should make policies that will further deepen the functions of the financial system to enhance Nigerian economic growth.